Ativismo e poéticas no espaço urbano: uma abordagem comunicacional do grupo BijaRi - Coutinho, Vanessa Espínola (2012)
The objective of the present research is to analyse and understand the potential of communication within urban spaces, focusing in particular on the artistic practices of the activist group BijaRi through práxis da comunicação (Barros, 2011); Our hypothesis is that activist actions have the potential to demonstrate a new critical perspectives about the construction of possible worlds. The impression of urban space according to Santos (2002), is to understand, the web of material and immaterial aspects and proposes considering the space as a hybrid or synthesis, always provisional between social content and spatial forms . Investigating these, this paper aims to reflect them in the sentence urban space communicates horizontally with the proposed communicational density presented by Santos (2008) and powered by the concept of fracture by Greimas (2002). Working with the case studies of interventions realized by the BijaRi group that question urban space and dialogue with the conceptual proposals, we seek to demonstrate the potential of communication that is made possible by artistic practices activists. Methodologically the project consists of four phases: Literature review, articulation of the concepts and field research with case studies and interviews. Finally we present the results including the conclusion as well as issues that have the potential for further research